If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-444=6(9x+16)
We move all terms to the left:
-444-(6(9x+16))=0
We calculate terms in parentheses: -(6(9x+16)), so:We get rid of parentheses
6(9x+16)
We multiply parentheses
54x+96
Back to the equation:
-(54x+96)
-54x-96-444=0
We add all the numbers together, and all the variables
-54x-540=0
We move all terms containing x to the left, all other terms to the right
-54x=540
x=540/-54
x=-10
| 2f=-18+3f | | -10c=-9c+7 | | -9=-1/3x+16 | | 14w-15=13w | | -11s+2=2-14s | | 3/x-1=6 | | 3g-10.72=2.2g-19.36 | | 132=100+n | | -12-7v=10-9v | | x-49=32 | | 10u=14+9u | | -8k=-4-7k | | -252=6(-10x+8) | | -9+4b=20-8b-5 | | 7(5a-4)-1=14-81 | | -5.5r-15.82=0.02+3.48+3.7r | | 38=4x=10 | | -9r-8+4r=-4r+2 | | 23=4y-1 | | 6=9x/9 | | z/3-9=-7 | | z-8=10z+10 | | 12+2(2x-2)=4(1+4x)-20 | | -9(6x-7)=441 | | 4+3w=24 | | 7+n=38 | | 7x+6=123 | | -19.73-3.6p=15.62-0.4p+11.37 | | 5,000−5x=0 | | 8.2j-12.87=-2.02+8.9j | | w–16=28 | | -24f=8 |